Cultural intelligence for effective performance in international assignments: implications for research & practice in cross-cultural HRD - Aahad, M. Osman-Gani; Ang, Soon (2009)
Although many studies were done in the past on expatriate adjustment issues, expatriate performance issues have not been addressed systematically, particularly from individual traits and capabilities perspectives by using relevant theories of intelligence. This paper presents a conceptual analysis of "cultural intelligence" (CQ) by describing the features of its four dimensions (four-factor model), which could be utilized for predicting managers' performance in international assignments. CQ is a multidimensional construct targeted at situations involving cross-cultural interactions arising from differences in race, ethnicity and nationality. The paper concludes by discussing the implications of CQ for future research and professional practice in HRD.